Staff Expectations of an Australian Integrated Model of Residential Rehabilitation for People With Severe and Persisting Mental Illness: A Pragmatic Grounded Theory Analysis - Meurk, Carla; Parker, Stephen; Newman, Ellie; Dark, Frances (Frontiers in Psychiatry, 2019)
Mental health services increasingly involve peer support workers. Staff expectations of working in these services are important because they frame processes and cultures that develop within services, and influence work satisfaction, staff retention and consumer experience. We examined staff expectations at two new community-based residential rehabilitation units trialling a staffing model where most staff are employed based on their lived experience of mental illness. Qualitative semi-structured interviews were conducted with ten peer support workers and five clinical staff on commencement at Community Care Units that opened in 2014 and 2015. Staff views covered individual motivations, emerging organisational practices and culture, and the nature and philosophy of recovery and recovery-oriented rehabilitation. Subtle differences were evident in staff understandings of recovery and recovery-oriented rehabilitation. Staff were mostly optimistic about the services’ potential but expressed uncertainty about how the professions would work together and practicalities of the new roles. Concerns that staff foreshadowed are consistent with those reported in the literature and can be pre-emptively addressed. Future research on staff experiences will enhance understanding of how staff perceptions of recovery-oriented rehabilitation change over time, and of how these relate to consumer experiences and outcomes.